Model of Charged Anisotropic Strange Stars in Minimally Coupled fR Gravity - H. Nazar; G. Abbas (Advances in Astronomy)
In the present article, we have investigated a new family of nonsingular solutions of static relativistic compact sphere which incorporates the characteristics of anisotropic fluid and electromagnetic field in the context of minimally coupled fR theory of gravity. The strange matter MIT bag model equation of state (EoS) has been considered along with the usual forms of the Karori–Barua KB metric potentials. For this purpose, we derived the Einstein–Maxwell field equations in the assistance of strange matter EoS and KB type ansatz by employing the two viable and cosmologically well-consistent models of fR=R+γR2 and fR=R+γRR+αR2. Thereafter, we have checked the physical acceptability of the proposed results such as pressure, energy density, energy conditions, TOV equation, stability conditions, mass function, compactness, and surface redshift by using graphical representation. Moreover, we have investigated that the energy density and radial pressure are nonsingular at the core or free from central singularity and always regular at every interior point of the compact sphere. The numerical values of such parameters along with the surface density, charge to radius ratio, and bag constant are computed for three well-known compact stars such as CS1SAXJ1808.4−3658 (x˜=7.07 km, CS2VelaX−1x˜=9.56 km, and CS34U1820−30x˜=10 km and are presented in Tables 1–6. Conclusively, we have noticed that our presented charged compact stellar object in the background of two well-known fR models obeys all the necessary conditions for the stable equilibrium position and which is also perfectly fit to compose the strange quark star object.